2015
DOI: 10.3109/23744235.2015.1107187
|View full text |Cite
|
Sign up to set email alerts
|

A long-term survey of brucellosis: Is there any marker to predict the complicated cases?

Abstract: Fever was the most significant predictive marker of complications. Other classical symptoms of brucellosis like myalgia and malaise were absent in most of the complicated cases. Blood culture was of limited value in the diagnosis of complicated cases most of the time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 21 publications
11
26
1
Order By: Relevance
“…However, there is no consensus in the literature regarding the optimal treatment approach for complicated cases. In a study carried out by Kayaaslan et al [8] , treatment duration for brucellosis patients with osteoarticular involvement ranged between four and six months. In a study by Kaptan et al [19] , patients with Brucella spondylodiscitis underwent treatment for 12-39 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there is no consensus in the literature regarding the optimal treatment approach for complicated cases. In a study carried out by Kayaaslan et al [8] , treatment duration for brucellosis patients with osteoarticular involvement ranged between four and six months. In a study by Kaptan et al [19] , patients with Brucella spondylodiscitis underwent treatment for 12-39 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Although complications vary in frequency, site of involvement, and presentation, osteoarticular complications are reported to be the most common type of complication in patients with brucellosis [8,14,27] . In a systematic review evaluating Brucellosis patients in Turkey, Calik and Gokengin [1] reported the rate of osteoarticular complications to be 43.74% (n=1839).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations